Hubungan Tingkat Pengetahuan Sikap Dan Tindakan Praktek Mandiri Bidan Dengan Pengelolaan Sampah Medis Studi Dilakukan Di Wilayah Kerja UPT Kesmas Blahbatuh I, Kecamatan Blahbatuh, Kabupaten Gianyar Tahun 2019 - Komang Jenny Melinda; Anysiah Elly Yulianti (Jurnal Kesehatan Lingkungan (JKL), 2019)
Abstract: Generally, medical waste which if produced from health support facilities, One of the health service which produces. Medical disposal is independent midwives. The purpose of the resedrch is find out. Any existences between knowledge level, behavour or attitudes in midwives independent practices regord to the medical waste management in the working area of the Blahbatuh I Public Health Unit, Blahbatuh. This research uses a cross sectional method. With the number of respondents at least 20 people. univariate and bivariat analysis wits results of the research which was invilved by 20 people respondents found . 55% have good knowledge, 60% have a good attitude, and 55% do enough behave. Based on the results of the bivariat analysis, there was a significant relationship between the level of knowledge (p=0.019), attitude (p= 0.047), action (p=0,000) with medical waste management. The level of relationship between the level of knowledge of 0.532 (moderate) attitude of 0.484 (moderate) action of 0.707 (strong) with the independent practice of midwives. The conclusion of this study is that there is a relationship between the level of knowledge, attitudes and actions of midwives' independent practices with medical waste management.